2021
DOI: 10.1007/s11664-020-08654-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of g-C3N4 with High Specific Surface Area and Photocatalytic Stability

Abstract: g-C 3 N 4 with porous structure has been synthesized by a thermal polymerization method and its specific surface area regulated by changing the calcination temperature. The as-prepared g-C 3 N 4 was characterized by x-ray diffraction (XRD) analysis, Fourier-transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), x-ray photoelectron spectroscopy (XPS), and ultraviolet-visible (UV-Vis) spectrophotometer. The photocatalytic activity of g-C 3 N 4 was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The measured specic surface areas of the synthesised nano-heterostructures gCT-1, gCT-0.75, gCT-0.50, gCT-0.25, and gCT-0.05 were 10.4, 16.7, 8.8, 5.7 and 3.8 m 2 g −1 , respectively. 75 The specic surface area (SSA) was estimated using BET equation for the gCT-0.75 composite and found to be 16.7 m 2 g −1 , which is a factor of 1.84-greater than that of the assynthesized Ti 3 C 2 T x (9.1 m 2 g −1 ). The increase in specic surface area (SSA) can be explained by the formation of a nanoheterostructure between Ti 3 C 2 T x and g-C 3 N 4 nanosheets, enlarging the interlayer spacing between the MXene multilayers aer increasing the content of g-C 3 N 4 in the composite.…”
Section: Surface Area Analysis (Using Bet Equation)mentioning
confidence: 99%
“…The measured specic surface areas of the synthesised nano-heterostructures gCT-1, gCT-0.75, gCT-0.50, gCT-0.25, and gCT-0.05 were 10.4, 16.7, 8.8, 5.7 and 3.8 m 2 g −1 , respectively. 75 The specic surface area (SSA) was estimated using BET equation for the gCT-0.75 composite and found to be 16.7 m 2 g −1 , which is a factor of 1.84-greater than that of the assynthesized Ti 3 C 2 T x (9.1 m 2 g −1 ). The increase in specic surface area (SSA) can be explained by the formation of a nanoheterostructure between Ti 3 C 2 T x and g-C 3 N 4 nanosheets, enlarging the interlayer spacing between the MXene multilayers aer increasing the content of g-C 3 N 4 in the composite.…”
Section: Surface Area Analysis (Using Bet Equation)mentioning
confidence: 99%
“…On that note, Jun and Shalom adopted a new method to synthesize bulk g-C 3 N 4 with a relatively high surface area (60-80 m 2 g −1 ) by utilizing the pre-organized supramolecular complex of melamine and cyanuric acid via topotactic transformation [64,65]. It is also reported that an increase in calcination temperature with a slower heating rate can marginally improve the surface area and crystallinity of g-C 3 N 4 [66].…”
Section: Bulky G-c 3 Nmentioning
confidence: 99%
“…High content of nitrogen in g-C3N4 offer plentiful of active-sites for redox reactions. Furthermore, g-C3N4 has a large theoretical surface area, stable structure, and composition similar to that of graphene [173,174]. However, due to serious stacking of g-C3N4 sheets, research is mainly focused on its composites with other capacitive materials [175].…”
Section: Crystallogens: Carbon Nitridementioning
confidence: 99%